Controlled arterial reflow after ischemia induces better outcomes in the juvenile rat brain. Issue 9 (September 2017) - Bonnin, Philippe; Pansiot, Julien; Paven, Elise; Eloi, Maxime; Renolleau, Sylvain; Baud, Olivier; Leger, Pierre-Louis; Charriaut-Marlangue, Christiane
Our objective was to determine whether controlled reflow on one side and/or the other side after bilateral carotid occlusion release could reduce cell death in focal ischemic P14 rats. Arterial blood flow was measured using ultrasonography. Cell death, inflammation and nitrotyrosine were measured using immunofluorescence. When reflow was first induced in the contralateral side, we observed improved outcome markers compared with those when reflow was first induced in the ipsilateral side and/or simultaneous reflow was induced in both sides. Our data suggest that progressive rerouting of arterial flow through the circle of Willis toward the ischemic site reduced cell death.